Networks among agricultural stakeholders in the southwestern highlands of Uganda - Fungo, B.; Clark, L.; Tenywa, M.M.; Tukahirwa, J.M.B.; Kamugisha, R.; Birachi, Eliud Abucheli; Wanjiku, C.; Bizoza, A.R.; Wimba, Benjamin M.M.; Pali, Pamela N.; Adewale, A.; Olowole, F. (2011)
The aim of this study was to explore the interactions that exist among agricultural stakeholders in the southwestern highlands of Uganda as a way of identifying opportunities and gaps for operation of Innovation Platforms (IPs) under the proof of concept of Integrated Agricultural Research for Development (IAR4D) research project. The specific objectives were to (i) characterize the agricultural stakeholders in the study sites (ii) determine the nature, diversity and relative importance of horizontal and vertical networks that exist among stakeholders in the Southwestern Highlands of Uganda. Data were collected from both stakeholder analysis and household interviews in Kabale and Kisoro Districts. Results show that extension staff, local governments and farmer groups accounted for approximately 75% of all categories of stakeholders in the area. Most of these organizations started after 10 to 15 years ago following the return of relative political stability in Uganda. Generally, stakeholder interactions in site with limited ARD intervention are more limited compared to their high-intervention counterparts. Sites with “good” market access have more institutions operating there but majority are isolated from each other. At household level, an individual household has networks with approximately two different organizations most of which are farmer groups or credit associations. The greatest proportion of horizontal networks that a household has is with fellow farmers. In order to make the value chain complete, establishment of IPs should pay special attention to including the private sector such as input and produce dealers. Facilitating IP actors to identify critical challenges and opportunities, and effectively articulate them will ensure cohesion. It is also critical to periodically monitor and evaluate stakeholders in terms of the quality of the networks to minimize conflict situations.